HARNESSING ARTIFICIAL INTELLIGENCE FOR GOVERNANCE EFFICIENCY IN FCT, ABUJA - Gbadebo, Adedeji D (Universitas Nasional, 2025)
This study explores the application of Artificial Intelligence (AI) in enhancing governmental efficiency within the Federal Capital Territory (FCT), Abuja, Nigeria. Anchored in the Socio-Technical Systems (STS) Theory, the research examines the interplay between technological innovation and sociopolitical structures in public governance. Employing a quantitative survey design, data were collected through structured questionnaires administered to 385 respondents selected via stratified random sampling. The data were analyzed using the chi-square statistical technique to test associations between key variables. The findings reveal that AI significantly improves decision-making processes and public service delivery, with 71% of respondents affirming its transformative potential in governance. However, the study identifies critical barriers, including inadequate infrastructure and insufficient technical expertise among public sector personnel. In response, the research advocates for the establishment of robust digital infrastructure, targeted AI capacity-building programs for government officials, and the ethical integration of AI systems. Furthermore, it recommends the implementation of pilot projects in strategic sectors such as healthcare, urban planning, and transportation to foster public trust and ensure inclusive adoption. The study contributes practical insights for policymakers, highlighting AI as a catalyst for transparent, responsive, and economically progressive governance in Abuja.